The Potential Role for Community Monitoring in MRV and in Benefit Sharing in REDD+ (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Developing countries interested in REDD+ under the UNFCCC have been requested to prepare a national forest monitoring system (NFMS) and a system to monitor, report and verify implementation (MRV). They have also been requested to engage local communities and indigenous groups as critical stakeholders in this process. The NFMS should be consistent with national inventories of emissions and removals of greenhouse gases. These inventories are, however, usually prepared using national level information with low geographical resolution and without the participation of local communities or other forest owners/managers. However, it has been shown that members of rural forest communities can develop the skills to monitor and measure levels of carbon stock in their forests and changes in these levels over time. If this information could be included and tracked from the local to regional and national levels, this might help to design transparent mechanisms for the assessment of REDD+ implementation, and possibly even for benefit sharing. The objective of this Special Issue is to discuss and explore the social, technical and political implications and potential of including community-based monitoring in MRV systems and benefit-sharing schemes in REDD+.